A Literature Survey of Green and Low-Carbon Economics Using Natural Experiment Approaches in Top Field Journal - Wu, Zhiyang; Zhao, Yu; Zhang, Ning (Green and Low-Carbon Economy, 2023)
The last 20 years or so have witnessed the academic torrent of natural experiments in environmental and climate change economics, and we have attempted to document this particular and important branch of economics. This paper reviews theoretical and empirical research in this branch using natural experiment approaches in field-top journals, including economic and scientific journals. We have organized and categorized the related papers into five major dimensions: content, identification strategies, regions, data, and theoretical models and channels. Statistics have found that causal inference and channel analysis on environmental externalities and related governance have endured for 20 years. Until about 10 years ago, a major shift towards diversification of research was taking place, with energy and low-carbon development themes making their way into these journals on the one hand, and developing countries, led by China, attracting attention because of their political systems and other factors. Identification strategies have also become more rigorous, as reflected in the identification concerns (e.g., omitted variables, selection, and reverse causation). Lastly, we also observe that the deep exploration of internal mechanisms and the availability of all types of data have dramatically impacted the traditional paradigm of economics. Received: 20 February 2023 | Revised: 23 March 2023 | Accepted: 3 April 2023 Conflicts of Interest Ning Zhang is the Editor-in-Chief for Green and Low-Carbon Economy, and was not involved in the editorial review or the decision to publish this article. The authors declare that they have no conflicts of interest to this work.